2017
DOI: 10.1016/j.cam.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Tikhonov regularization with a nonlinear penalty term

Abstract: Tikhonov regularization is one of the most popular methods for solving linear systems of equations or linear least-squares problems with a severely ill-conditioned matrix and an errorcontaminated data vector (right-hand side). This regularization method replaces the given problem by a penalized least-squares problem. It is well known that Tikhonov regularization in standard form may yield approximate solutions that are too smooth, i.e., the computed approximate solution may lack many details that the desired s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Applying the fractional Tikhonov method given by Morigi et al, 23 we propose the following regularized solution with exact data (h, f):…”
Section: Fractional Tikhonov Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the fractional Tikhonov method given by Morigi et al, 23 we propose the following regularized solution with exact data (h, f):…”
Section: Fractional Tikhonov Methodsmentioning
confidence: 99%
“…Applying the fractional Tikhonov method given by Morigi et al, we propose the following regularized solution with exact data false(sans-serifh,monospaceffalse): scriptGμ,ϑ(x)=sans-serifq=0Eβ,11sans-serifasans-serifqnormalγnormalβsans-serifToβγEβ,12sans-serifasans-serifqnormalγnormalβsans-serifToβγEβ,12sans-serifasans-serifqnormalγnormalβsans-serifToβγ+μϑΘ,sans-serife^sans-serifqsans-serife^sans-serifq. If the observation data false(sans-serifh,monospaceffalse) is noised by false(hε,fεfalse), then we have Gμ,ϑε(x)=sans-serifq=0Eβ,11…”
Section: Fractional Tikhonov Regularizationmentioning
confidence: 99%
“…Tikhonov et al [21]. Related research on fractional regularization methods can refer to the literature [22][23][24][25][26][27][28][29]. The fractional Tikhonov method with the a priori parameter for the same analytic continuation problem has been researched by [30].…”
Section: Problemmentioning
confidence: 99%
“…The discrepancy principle is an example of the first type and the Cross-Validation and L-curve are examples from the second type (see [23]). Since it has been observed that x δ α oversmoothens the solution x [12], the Fractional Tikhonov regularization (FTR) method [1,2,7,[10][11][12]19] was considered, wherein the minimizer x δ α,β of the functional…”
Section: Introductionmentioning
confidence: 99%